Upper visual field distractors preferentially bias attention to the left. (March 2015) - Thomas, Nicole A.; Castine, Benjamin R.; Loetscher, Tobias; Nicholls, Michael E.R.
Abstract: Pseudoneglect is influenced by vertical visual field stimulation, such that attentional biases are stronger for upper space distractors. Leftward biases result from right hemisphere visuospatial processing, and may be accentuated by additional right hemisphere activation during upper space distraction. Three experiments examined potential explanations for this finding. Experiment 1 controlled for perceptual grouping and leftward biases remained stronger in upper space. Experiment 2 used peripheral distractors to eliminate two further potential explanations: centre-of-mass and framing effects. Eye tracking was included to compare overt and covert attention. Findings supported the occurrence of a stronger leftward attentional bias during upper space distraction. Distractors were rarely fixated, suggesting covert attentional mechanisms are preferentially drawn toward upper space distractors. Experiment 3 employed a cueing paradigm that purposefully directed attention away from centre to determine whether pseudoneglect was influenced by overt attentional orienting. Results indicated that when attention was overtly directed away from centre, the strength of pseudoneglect did not differ based on visual field. It is concluded that covert attention toward upper space distractors recruits additional right hemisphere activation, leading existing leftward biases to be accentuated.